40Ar/39Ar geochronological evidence for multiple magmatic events during the emplacement of Tapira alkaline-carbonatite complex, Minas Gerais, Brazil. (January 2020) - Conceição, Fabiano T.; Vasconcelos, Paulo M.; Godoy, Letícia H.; Navarro, Guillermo R.B.
Abstract: The Alto Parnaíba Igneous Province (APIP) is a voluminous magmatic province composed of various alkaline-carbonatite complexes emplaced in the Brasilia Mobile Belt during the Cretaceous. Relative timing of emplacement of silicate and carbonate magmas in most of these complexes remains mostly unresolved due to conflicting geochronological results. To determine the duration of magmatism and to test the possible existence of multiple magmatic events, we employ 40 Ar/ 39 Ar phlogopite single crystal dating to determine the history of magma emplacement at the Tapira alkaline-carbonatite complex, Minas Gerais, Brazil. The new single crystal data indicate at least two magmatic events during the emplacement of this complex, the first at > 96.2 ± 0.8 Ma and the second at 79.15 ± 0.6 Ma. The first igneous event was responsible for emplacement of the silicate plutonic series, while the second event corresponds to the emplacement of primarily carbonatitic magmas, generating metasomatic phlogopite alteration in bebedourites. The ages of intrusion and cooling of the alkaline-carbonatite complexes in the APIP must be investigated in other complexes to determine if intrusion intervals of 17 Ma or more are common regionally. Protracted intrusive events, if related to magma generation by passage of South America over a stationary Trindade plume, requires complex ponding and lateral magma flow below a slow-moving continent. Highlights: Multiple magmatic events at the Tapira alkaline-carbonatite complex were measured. A first event at 96 Ma was responsible for emplacement of the silicic magma. The second event at 79 Ma corresponds to the emplacement carbonatitic magma. The range of the alkaline-carbonatite magmatism in the APIP is at least 17 Ma.